Patient‐centered Outcomes Research in Emergency Care: Opportunities, Challenges, and Future Directions. (24th March 2016) - Rising, Kristin L.; Carr, Brendan G.; Hess, Erik P.; Meisel, Zachary F.; Ranney, Megan L.; Vogel, Jody A.
Abstract: The Patient‐Centered Outcomes Research Institute (PCORI) was established by Congress in 2010 to promote the conduct of research that could better inform patients in making decisions that reflect their desired health outcomes. PCORI has established five national priorities for research around which specific funding opportunities are issued: 1) assessment of prevention, diagnosis, and treatment options; 2) improving healthcare systems; 3) communication and dissemination research; 4) addressing disparities; and 5) improving methods for conducting patient‐centered outcomes research. To date, implementation of patient‐centered research in the emergency care setting has been limited, in part because of perceived challenges in meeting PCORI priorities such as the need to focus on a specific disease state or to have planned follow up. We suggest that these same factors that have been seen as challenges to performing patient‐centered research within the emergency setting are also potential strengths to be leveraged to conduct PCORI research. This paper explores factors unique to patient‐centered emergency care research and highlights specific areas of potential alignment within each PCORI priority.